2008
DOI: 10.1080/10412905.2008.9700030
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antimicrobial Activity of Volatile Components ofScorzonera undulata

Abstract: The volatile constituents of the aerial parts of Scorzonera undulata Vahl subsp. deliciosa (Guss.) Maire obtained by steam distillation were analyzed by GC and GC/MS. Thirty six constituents were identified in the oil and the main components of which were methyl hexadecanoate (30.4%), methyl linolenate (23.9%) and heneicosane (12.2%) The antimicrobial activity of the oil was also investigated. The Scorzonera undulata subsp. deliciosa oil exhibited an interesting antibacterial activity against Gram-positive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The authors suggest that greater activity against Gram-positive bacteria strains could be caused by easier penetration through the lipophilic cell membranes by hydrophobic ingredients of the oil. Unfortunately, no reference compound was assessed together with the oil, thus it is difficult to compare those results with any known antibacterial substances [ 90 ].…”
Section: Biological Activitymentioning
confidence: 99%
“…The authors suggest that greater activity against Gram-positive bacteria strains could be caused by easier penetration through the lipophilic cell membranes by hydrophobic ingredients of the oil. Unfortunately, no reference compound was assessed together with the oil, thus it is difficult to compare those results with any known antibacterial substances [ 90 ].…”
Section: Biological Activitymentioning
confidence: 99%
“…Previous phytochemical investigation on Scorsonera species showed that the main constituents of the aerial parts of S. undulata oil from Tunisia were the aliphatic esters and aliphatic hydrocarbons [3]. The main components of S. hispanica from Netherlands were aliphatics acid and aliphatic hydrocarbons [4], while aliphatic hydrocarbons and alcohols were the main constituents of S. mongolica oil from China [5].…”
Section: Introductionmentioning
confidence: 99%
“…Phenols are said to offer resistance to diseases and pests in plants. Grains containing high amount of polyphenols are resistant to bird attack [22]. Interestingly, phytochemical screening of the current investigation has revealed that extracts from both the plant parts possess at least three to four of the following classes of secondary metabolites: phenols, flavonoids, terpenoids, tannins, alkaloids and saponins.…”
Section: Resultsmentioning
confidence: 78%